The Heathrow Case in the Supreme Court: climate change legislation and administrative adjudication - Bell, J; Fisher, E (Wiley, 2022)
In R (on the application of Friends of the Earth Ltd and others) v Heathrow Airport Ltd the UK Supreme Court allowed an appeal against the Court of Appeal's decision that there had been a series of legal errors in the designation of the Airport National Policy Statement. This case note analyses the case from an ‘internal’ doctrinal perspective and argues that the Supreme Court could have engaged more explicitly with the legal issues that arise from climate change legislation for administrative law adjudication. For courts to adjudicate well in such circumstances they need to be prepared to develop administrative law doctrine, particularly in light of the issues of integrating climate change into public decision-making and of scientific/policy uncertainty which lie in the background of climate change legislation.